Conversion Degree of Indirect Resin Composites and Effect of Thermocycling on Their Physical Properties - Souza, Rodrigo O. A. [UNESP]; Oezcan, Mutlu; Michida, Silvia M. A. [UNESP]; Melo, Renata M. de [UNESP]; Pavanelli, Carlos Augusto [UNESP]; Bottino, Marco A. [UNESP]; Soares, Luis E. S.; Martin, Airton A. (Wiley-Blackwell, 2010)
Purpose: This study evaluated the degree of conversion (DC) of four indirect resin composites (IRCs) with various compositions processed in different polymerization units and investigated the effect of thermal aging on the flexural strength and Vicker's microhardness.Materials and Methods: Specimens were prepared from four IRC materials, namely Gr 1: Resilab (Wilcos); Gr2: Sinfony (3M ESPE); Gr3: VITA VMLC (VITA Zahnfabrik); Gr4: VITA Zeta (VITA Zahnfabrik) using special molds for flexural strength test (N = 80, n = 10 per group) (25 x 2 x 2 mm(3), ISO 4049), for Vicker's microhardness test (N = 80, n = 10 per group) (5 x 4 mm(2)) and for DC (N = 10) using FT-Raman Spectroscopy. For both flexural strength and microhardness tests, half of the specimens were randomly stored in distilled water at 37 degrees C for 24 hours (Groups 1 to 4), and the other half (Groups 5 to 8) were subjected to thermocycling (5000 cycles, 5 to 55 +/- 1 degrees C, dwell time: 30 seconds). Flexural strength was measured in a universal testing machine (crosshead speed: 0.8 mm/min). Microhardness test was performed at 50 g. The data were analyzed using one-way and two-way ANOVA and Tukey's test (alpha = 0.05). The correlation between flexural strength and microhardness was evaluated with Pearson's correlation test (alpha = 0.05).Results: A significant effect for the type of IRC and thermocycling was found (p = 0.001, p = 0.001) on the flexural strength results, but thermocycling did not significantly affect the microhardness results (p = 0.078). The interaction factors were significant for both flexural strength and microhardness parameters (p = 0.001 and 0.002, respectively). Thermocycling decreased the flexural strength of the three IRCs tested significantly (p < 0.05), except for VITA Zeta (106.3 +/- 9.1 to 97.2 +/- 14 MPa) (p > 0.05) when compared with nonthermocycled groups. Microhardness results of only Sinfony were significantly affected by thermocycling (25.1 +/- 2.1 to 31 +/- 3.3 Kg/mm(2)). DC values ranged between 63% and 81%, and were not significantly different between the IRCs (p > 0.05). While a positive correlation was found between flexural strength and microhardness without (r = 0.309) and with thermocycling (r = 0.100) for VITA VMLC, negative correlations were found for Resilab under the same conditions (r = -0.190 and -0.305, respectively) (Pearson's correlation coefficient).Conclusion: Although all four IRCs presented nonsignificant DC values, flexural strength and microhardness values varied between materials with and without thermocycling.
Keywords: Degree of conversion; flexural strength; indirect resin composites; Vicker's hardness